Challenges of Female Entrepreneurs in Transition Countries: Case Study of Kosovo - Rrezarta Gashi; Hana Gashi (Prizren Social Science Journal, 2019)
Opportunely in the time of globalization, female entrepreneurs, including those doing business in countries in transition, are moving towards the booming of their businesses. Apart from the advantages they have in the period their countries are transitioning, female entrepreneurs also are faced with many challenges. These challenges are faced by female entrepreneurs who are doing business in Kosovo, which is in a transition period. The challenges faced by female entrepreneurs in the state of Kosovo, apart from economic factors, are also cultural factors. Given the role of small businesses in the country's economic development, a number of these businesses are run by women, ventures also known as small businesses.